The environmental footprint of available food waste in young households: A diary case study of Schleswig-Holstein (Germany) - Bente Castro Campos; Aravindi Muthuwahandi; Yanjun Ren; Jens-Peter Loy (German Journal of Agricultural Economics (GJAE), 2024)
As households contribute significantly to food waste, it can be assumed that they bear considerable responsibility for the environmental footprint of it. In Germany, household food waste comprises over half of all food loss and waste, with a notable share attributable to young people. To explore their environmental footprint, data from fifty young households in Schleswig-Holstein, northern Germany, is analyzed using the Food Loss and Waste Value Calculator with an integrated life cycle assessment. We evaluate the environmental footprint of animal and plant food waste across five categories: climate change, water scarcity footprint, soil quality index, phosphorus and nitrogen eutrophication. Surprisingly, animal food waste, though representing only 18% of the total volume of all available food waste in our study, exhibits a more substantial impact in all categories except water scarcity. Specifically, animal food waste is found to be an important factor in soil degradation. Our results generally indicate an inverse relationship between the volume of animal-based and plant-based food waste in young households and its environmental footprint. However, the case study highlights a troubling connection between plant food waste and significant water scarcity issues in European agriculture.
Keywords: 330; Climate Change; Eutrophication; Food Loss and Waste Value Calculator; Life Cycle Assessment; Soil Quality; Water Scarcity